To simplify the expression \((4^3 \cdot 7^{-2})^{-5} / (7^9 \cdot 4^{-13})\), we will apply the rules of exponents step by step.
-
Apply the power of a product rule: \((a \cdot b)^n = a^n \cdot b^n\)
\[ (4^3 \cdot 7^{-2})^{-5} = 4^{3 \cdot -5} \cdot 7^{-2 \cdot -5} = 4^{-15} \cdot 7^{10} \]
So, we have: \[ \frac{4^{-15} \cdot 7^{10}}{7^9 \cdot 4^{-13}} \]
-
Rewrite the expression: \[ = \frac{4^{-15}}{4^{-13}} \cdot \frac{7^{10}}{7^9} \]
-
Apply the quotient of powers rule: \(\frac{a^m}{a^n} = a^{m-n}\)
For \(4\): \[ \frac{4^{-15}}{4^{-13}} = 4^{-15 - (-13)} = 4^{-15 + 13} = 4^{-2} \]
For \(7\): \[ \frac{7^{10}}{7^{9}} = 7^{10 - 9} = 7^{1} = 7 \]
So we have: \[ 4^{-2} \cdot 7 = \frac{7}{4^2} \]
-
Simplify further: \[ 4^2 = 16 \]
Therefore: \[ \frac{7}{16} \]
So the final answer, simplified with only positive exponents, is: \[ \frac{7}{16} \]